Role of glycogen in control of glycolysis and IMP formation in human muscle during exercise - Spencer, M K; Katz, A (The American journal of physiology, 1991)
The effect of prior glycogen depletion on glycolysis [flux through phosphofructokinase (PFK)] and inosine monophosphate (IMP) formation in human skeletal muscle has been investigated. Eight subjects cycled at a work load calculated to elicit 95% of maximal O2 uptake on two occasions, the first to fatigue [5.5 +/- 0.3 (SE) min] and the second at the same workload and for the same duration as the first. Before the first experiment, muscle glycogen stores were lowered by a combination of exercise and diet. Before the second experiment, muscle glycogen stores were supercompensated. In the low-glycogen (LG) state muscle glycogen decreased from 201 +/- 31 mmol glucosyl units/kg dry wt at rest to 105 +/- 28 after exercise, and in the high-glycogen (HG) state from 583 +/- 40 to 460 +/- 49. The accumulation of fructose 6-phosphate (F-6-P; activator of PFK) during exercise was markedly attenuated in the LG state (P less than 0.01), whereas lactate accumulation in muscle was similar between treatments, suggesting that muscle pH was also similar. Glycolysis (estimated from glycogenolysis minus accumulation of hexose monophosphates) was not measurably different between treatments (LG = 88 +/- 17, HG = 106 +/- 43 mmol/kg dry wt; P greater than 0.05). IMP was significantly greater in the LG state after exercise (3.63 +/- 0.85 vs. 1.97 +/- 0.44 mmol/kg dry wt; P less than 0.05). It is concluded that decreased glycogen availability does not measurably alter the rate of muscle glycolysis during intense exercise. It is hypothesized that the attenuated increase in F-6-P in the LG state, which should theoretically decrease glycolysis, is compensated for by increases in free ADP and AMP (activators of PFK) at the enzymatic site during the contraction phase. The greater increase in IMP in the LG state is consistent with this hypothesis, since ADP and AMP are also activators of AMP deaminase.